Spinal Cord Injury and Pressure Ulcer Prevention: Using Functional Activity in Pressure Relief. (9th April 2013) - Stinson, May; Schofield, Rachel; Gillan, Cathy; Morton, Julie; Gardner, Evie; Sprigle, Stephen; Porter-Armstrong, Alison
Abstract : Background . People with spinal cord injury (SCI) are at increased risk of pressure ulcers due to prolonged periods of sitting. Concordance with pressure relieving movements is poor amongst this population, and one potential alternative to improve this would be to integrate pressure relieving movements into everyday functional activities. Objectives. To investigate both the current pressure relieving behaviours of SCI individuals during computer use and the application of an ergonomically adapted computer-based activity to reduce interface pressure. Design. Observational and repeated measures design. Setting. Regional Spinal Cord Injury Unit. Participants. Fourteen subjects diagnosed with SCI (12 male, 2 female). Intervention. Comparing normal sitting to seated movements and induced forward reaching positions. Main Outcome Measures. Interface pressure measurements: dispersion index (DI), peak pressure index (PPI), and total contact area (CA). The angle of trunk tilt was also measured. Results. The majority of movements yielded less than 25% reduction in interface pressure compared to normal sitting. Reaching forward by 150% of arm length during an adapted computer activity significantly reduced DI (P < 0.05 ), angle of trunk tilt (p<0.05), and PPI for both ischial tuberosity regions (P < 0.001 ) compared to normal sitting. Conclusion. Reaching forward significantly redistributed pressure at the seating interface, as evidenced by the change in interface pressures compared to upright sitting.